2022
DOI: 10.30604/jika.v7i2.1006
|View full text |Cite
|
Sign up to set email alerts
|

The Empowerment of Family in Effort to Reduce Stunting in Under-Five Children: A Scoping Review

Abstract: Stunting is a chronic nutrition problems causing growth failures in under five years old children. The condition does not only affect physical growth but also brain intelligence which leads to the low quality of human resources and eventually affects national economy. Family empowerment efforts can be one of effective ways to help the government in decreasing stunting case. The study was to review family empowerment in stunting declining efforts in under five years old children. The study applied PRISM-ScR fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…They become more interactive both professionally and socially and allow for more effective collaboration (Coufal & Woods, 2018). The results of research conducted by Annisa & Sulistyaningsih concluded that one of the important elements in reducing the risk of stunting through family empowerment is by paying attention to environmental hygiene such as using healthy latrines, sanitation, personal hygiene by parents, and improving environmental health (Annisa & Sulistyaningsih, 2022).…”
Section: Results Of Individual Sources Of Evidencementioning
confidence: 99%
“…They become more interactive both professionally and socially and allow for more effective collaboration (Coufal & Woods, 2018). The results of research conducted by Annisa & Sulistyaningsih concluded that one of the important elements in reducing the risk of stunting through family empowerment is by paying attention to environmental hygiene such as using healthy latrines, sanitation, personal hygiene by parents, and improving environmental health (Annisa & Sulistyaningsih, 2022).…”
Section: Results Of Individual Sources Of Evidencementioning
confidence: 99%
“…[ 4 ] Stunting is an outcome of various factors resulting from adverse social and economic situations such as difficulties in obtaining food, unemployment that identifies an irregular form of income for the family, limited access to education and health services, or illness caused by illness unhygienic conditions. [ 10 11 12 ] It also includes unpleasant circumstances and unequal access and allocation of resources among the family members.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have also been supported by several previous studies obtained earlier. Annisa said that stunting is a chronic nutritional problem causing growth and development disorders in children under five(Annisa, & Sulistyaningsih, 2022). Family empowerment efforts can be oneof the effective ways to help the government reduce stunting cases.…”
mentioning
confidence: 99%